The guid Scots tongue - MacNeil, Robert (Sydney, NSW. : BBC Education & Training, 1986)
Shows the effect of the Scot.
Copy available in DVD format.
Keywords: English language -- Dialects -- Scotland; English language -- Foreign elements -- Scots; Scots language; Language spread